Multi-omics dissection of MAPK-driven senescence unveils therapeutic vulnerabilities in KIAA1549::BRAF-fusion pediatric low-grade glioma models - Sigaud, Romain; Stefanski, Anja; Selt, Florian; Kocher, Daniela; Usta, Diren; Picard, Daniel; Büdenbender, Isabel; Remke, Marc; Pfister, Stefan; Jones, David T. W.; Brummer, Tilman; Witt, Olaf; et al. (Signal transduction and targeted therapy, 2025)
Pilocytic astrocytomas (PA), the most common pediatric low-grade gliomas (pLGGs), are characterized by genetic MAPK pathway alterations leading to constitutive activation and oncogene-induced senescence (OIS) accompanied with the senescence-associated secretory phenotype (SASP). This study investigates the molecular mechanisms of signaling pathways regulating OIS and SASP in pLGGs using a multi-omics approach. We utilized senescent DKFZ-BT66 cells derived from a primary KIAA1549::BRAF-fusion positive PA to generate RNA-sequencing and phospho-/proteomic datasets before and after treatment with the MEK inhibitor trametinib. Multi-omics factor analysis (MEFISTO) and single sample gene set enrichment analysis (ssGSEA) were employed to identify key OIS effectors and differentially regulated pathways upon MAPK inhibition. Trametinib treatment inhibited MAPK activity, OIS and SASP signatures across all omics levels, functionally underscored by reduced sensitivity towards senolytic drugs. We constructed a pathway network using a prior knowledge approach, mapping n = 106 upregulated and n = 84 downregulated direct downstream effectors of MAPK leading to OIS/SASP. These effectors are associated with better progression-free survival in pLGG patients, independent of tumor site, level of resection, and genetic aberration. Several compounds targeting signaling nodes (SOD-1, IRS1, CDK1/2, CK2) involved in OIS and under MAPK control were identified, of which n = 4 were validated in an additional primary KIAA1549::BRAF fusion pLGG model as potential new therapeutic vulnerabilities for the treatment of pLGG. Our unbiased multi-omics signaling pathway analysis identifies a specific and comprehensive network of MAPK-OIS-SASP interdependencies in pLGGs and suggests new therapeutic strategies for these tumors.
Gesehen am 12.01.2026